Penggunaan Modul Esp32 Cam Faedah Pembuangan Sampah Sembarangan Guna Penertiban Dan Kepatuhan Masyarakat Menggunakan Arduino Mega 2560 Dan Internet Of Things - Ayu Fazzira Yuskar; Emil Naf'an; Okta Andrica Putra (Journal of Computer Scine and Information Technology, 2024)
The advancement of science and technology motivates humans to address environmental issues, including environmental cleanliness. Waste, as one of the main problems, poses a serious threat to humans and the environment. Indonesia, as the world's second largest waste contributor, faces significant challenges, particularly from traditional markets. This issue requires active participation and awareness of traders, as well as government action in enforcing regulations. Robotics technology and the Internet of Things (IoT) offer innovative solutions. The use of microcontrollers and ESP32 CAM modules can help detect and monitor littering perpetrators. This system utilizes ultrasonic sensors and PIR sensors to detect motion and distance. Thus, community compliance with waste management regulations can be enhanced through effective monitoring and enforcement.This research aims to design a system based on Arduino Mega 2560 and IoT to improve community discipline and awareness.